2022
DOI: 10.1088/1755-1315/1032/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater quality assessment and its insinuations in some parts of Aheri taluka dist. - Gadchiroli, Maharashtra

Abstract: Aheri tehsil of Gadchiroli district in the Indian state of Maharashtra is located on the bank of the Pranhita River, a side stream of the Godavari River. In the present study, total five villages from Aheri taluka were selected to collect groundwater samples. A total number of 25 samples were collected, where five samples represent each village. This study is concerned with physicochemical parameters mainly electrical conductivity, total dissolved solids, temperature, chloride, fluoride, total hardness, pH, ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The western boundary of Wardha district is marked along the Wardha river, which is trapped near Kavith village and receives outfall from Bembla dam in Yavatmal district, Maharashtra. The correlation in the concentrations of various parameters also suggests the presence of salts due to the intrusion of urban waste in the groundwater (Peddiwar et al, 2022). The variations in the characteristics of groundwater suggested that the potential sources of pollutants could be either from the study area or from adjoining districts, as the geology of Wardha district allows wastewater discharge from nearby districts.…”
Section: Spatial Distribution Of Groundwater Parametersmentioning
confidence: 93%
“…The western boundary of Wardha district is marked along the Wardha river, which is trapped near Kavith village and receives outfall from Bembla dam in Yavatmal district, Maharashtra. The correlation in the concentrations of various parameters also suggests the presence of salts due to the intrusion of urban waste in the groundwater (Peddiwar et al, 2022). The variations in the characteristics of groundwater suggested that the potential sources of pollutants could be either from the study area or from adjoining districts, as the geology of Wardha district allows wastewater discharge from nearby districts.…”
Section: Spatial Distribution Of Groundwater Parametersmentioning
confidence: 93%